Pengaruh Digital Influencer @dokterdetektifhero Terhadap Tingkat Kepercayaan Konsumen dalam Pengambilan Keputusan Pembelian Produk Skincare - Hasna Ayu Wulandari; Muhammad Thoyib Amali (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
The growing use of digital influencers in the skincare industry has made social media an important source of information for consumers in making purchasing decisions. However, the emergence of overclaim issues in skincare products has positioned consumer trust as a crucial factor in the decision-making process. This study aims to examine the influence of the TikTok digital influencer account @dokterdetektifhero on skincare purchasing decisions through consumer trust as a mediating variable. A quantitative approach with a survey method was employed. Data were collected through questionnaires distributed to 120 respondents who had viewed @dokterdetektifhero’s content and were interested in skincare products. The sampling technique used was purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. This study adopted the Elaboration Likelihood Model to explain how consumers process persuasive messages delivered by digital influencers in shaping trust and purchasing decisions. The results indicate that digital influencers have a positive and significant effect on consumer trust and purchasing decisions. Consumer trust also has a positive and significant effect on purchasing decisions. Furthermore, consumer trust was found to mediate the relationship between digital influencers and purchasing decisions through partial mediation. The findings demonstrate that the educational content and credibility of @dokterdetektifhero are capable of building consumer trust, which in turn encourages skincare purchasing decisions.